Use of Web 2.0 in learning process: a comparison between quantity surveying and Information Technology undergraduates - Tan, Chin Keng; Yeoh, Kah Ching (2013)
Many emerging web based applications and technologies are increasingly being implemented in learning institutions to enhance students’ learning experience in recent year. This paper aims to provide an overall picture of the level of usage as well as the different in pattern of educational related Web 2.0 by Quantity Surveying (QS) undergraduates and Information Technology (IT) undergraduates. The data for this survey were collected from QS undergraduates and IT undergraduates from two higher education institutions in Malaysia. SPSS was utilized as a main tool to analyze data. The results of the present study indicate that QS undergraduates and IT undergraduates in Malaysia generally have a positive attitude towards the use of Web 2.0 applications in their studies. Both QS and IT undergraduates generally have high usage in web search, social networking website, e-learning portal, educational video sharing site and web translator but low usage in portfolio and podcast.